Equipoise in Management of Patients With Acute Symptomatic Carotid Stenosis (Hot Carotid). Issue 1 (February 2021) - Ganesh, Aravind; Bartolini, Luca; Singh, Ravinder-Jeet; Al-Sultan, Abdulaziz S.; Campbell, David J.T.; Wong, John H.; Menon, Bijoy K.
Abstract : Objective: To explore differences in antithrombotic management of patients with acutely symptomatic carotid stenosis ("hot carotid") awaiting revascularization with endarterectomy or stenting (CEA/CAS). Methods: We used a worldwide electronic survey with practice-related questions and clinical questions about 3 representative scenarios. Respondents chose their preferred antithrombotic regimen (1) in general, (2) if the patient was already on aspirin, or (3) had associated intraluminal thrombus (ILT) and identified clinical/imaging factors that increased or decreased their enthusiasm for additional antithrombotic agents. Responses among different groups were compared using multivariable logistic regression. Results: We received 668 responses from 71 countries. The majority favored CT angiography (70.2%) to evaluate carotid stenosis, CEA (69.1%) over CAS, an aspirin-containing regimen (88.5%), and a clopidogrel-containing regimen (64.4%) if already on aspirin. Whereas diverse antithrombotic regimens were chosen, monotherapy was favored by 54.4%–70.6% of respondents across 3 scenarios. The preferred dual therapy was low-dose aspirin (75–100 mg) plus clopidogrel (22.2%) or high-dose aspirin (160–325 mg) plus clopidogrel if already on aspirin (12.2%). Respondents favoring CAS more often chose ≥2 agents (adjusted odds ratio [aOR] vs CEA: 2.00, 95% confidence interval 1.36–2.95, p = 0.001) or clopidogrel-containing regimens (aOR: 1.77, 1.16–2.70, p = 0.008). Regional differences included respondents from Europe less commonly choosing multiple agents if already on aspirin (aOR vs United States/Canada: 0.57, 0.35–0.93, p = 0.023), those from Asia more often favoring multiple agents (aOR: 1.95, 1.11–3.43, p = 0.020), vs those from the United States/Canada preferentially choosing heparin-containing regimens with ILT (aOR vs rest: 3.35, 2.23–5.03, p < 0.001). Factors increasing enthusiasm for ≥2 antithrombotics included multiple TIAs (57.2%), ILT (58.5%), and ulcerated plaque (57.4%); 56.3% identified MRI microbleeds as decreasing enthusiasm. Conclusions: Our results highlight the heterogeneous management and community equipoise surrounding optimal antithrombotic regimens for hot carotids.